THE DEVELOPMENT OF EVALUATION INDICATORS FOR BACHELOR’S DEGREE CURRICULUM IN BUSINESS ADMINISTRATION AT SOUPHANOUVONG UNIVERSITY, LAO PEOPLE’S DEMOCRATIC REPUBLIC - Nortoualee, Suelue; Samuttai, Ruetinan; Damrongpanit, Suntonrapot (Life Sciences and Environment Journal, 2017)
This study aims 1) to develop the evaluation indicators for bachelor’s degree curriculum in Business Administration, Management Program, Faculty of Economics and Tourism at Souphanouvong University and 2) to test the quality of the evaluation indicators for bachelor’s degree curriculum in the Business Administration, Management Program, Faculty of Economics and Tourism at Souphanouvong University. The samples of 205 participants included administrators, lecturers and relevant experts. The data was collected by a five-point rating scale for the questionnaire. Mplus program version 7.4 was used for quality test for indicators confirmatory factor analysis. The results showed that 1) there are 3 factors 17 indicators to assess the bachelor’s degree curriculum in the Business Administration, Management Program, Faculty of Economics and Tourism at Souphanouvong University and 2) the structural relationship model of the evaluation indicators for bachelor’s degree curriculum in the Business Administration Program of the Faculty of Economics and Tourism at Souphanouvong University was appropriately aligned and consistent with the empirical data in c2=113.161; df=112; p-Value=0.4515 not statistically significant; inc2/df=1.01; RMSEA=0.008; CFI=0.999; TLI=0.999 and SRMR=0.05. The factor loading of the three latent variables valued0.766-0.947 .The factor loading of the seventeen observed variables valued 0.498-0.951and significant difference at the 0.01 level.